Cognitive Aging in Parents of Children with Disabilities. (24th March 2015) - Song, Jieun; Mailick, Marsha R.; Greenberg, Jan S.; Ryff, Carol D.; Lachman, Margie E.
Abstract : Objective: This study examines the cognitive functioning of parents of children with disabilities, specifically, whether there is an evidence of accelerated cognitive aging among these parents. In addition, the study investigates the moderating influences of two variables: parents' gender and stress from negative parenting experience. Method: The analyses utilize data from the National Survey of Midlife in the United States (2005). The analytic sample consisted of two groups of parents, who completed the cognitive battery, the interview, and the mail-back survey: 128 parents who had children with childhood-onset disabilities and 512 matched comparison parents who had only nondisabled children. Results: Age differences in episodic memory were more pronounced among mothers of children with disabilities than among mothers with nondisabled children, especially among mothers with higher levels of negative parenting experience. In contrast, there were no interaction effects of parenting status, age, and negative parenting experience among fathers. Discussion: The results show that parenting children with disabilities over a prolonged period of time jeopardizes cognitive function (especially memory) among older mothers, possibly via the mechanism of heightened parenting stress due to higher levels of negative parenting experience.